Ahamoniylarning O’rta Osiyodagi davlat boshqaruvi shakli - SH.Suyunova, S.Elmurodova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article examines the state administration system of the Achaemenid dynasty in Central Asia. Kopro pays attention to the people of Strabia, the development of tax and trade routes. The article analyzes the relations of the Achaemenids with the local population, their respect for their cultural and religious mothers.